Bioinformatic Prediction of Depression-Related Signaling Pathways Regulated by miR-146a in Peripheral Blood of Patients with Post-Stroke Depression: Depression-Related Signaling Pathways Regulated by miR-146a - Chen, Zhimin; Wang, Na; Na, Risu; Yu, Haiyan; Sui, Dan; Cui, Bing; Wang, Lihua (Cellular and Molecular Biology, 2022)
It was aimed to explore the differential expression of miR-146a-5p in peripheral blood of patients with post-stroke depression (PSD), and to analyze its mechanism using bioinformatics. Stroke patients were selected as the research objects, and were divided into PSD ones and non-post-stroke depression (N-PSD) ones with the National Institutes of Health stroke scale (NHISS) and Hamilton Depression Scale-17 terms (HAMD-17) scores. Peripheral blood of patients was collected for serum miR-146a-5p detection. Targetscan7.1, miRDB, DIANA TOOLS, and more databases were used to predict the target genes of miR-146a-5p. String11.0 was applied to construct a protein interaction network, and GO and KEGG pathway enrichment analysis of target genes was performed. Compared with that of N-PSD patients, serum miR-146a-5p levels in PSD patients were significantly increased (P<0.05). The receiver operator characteristic (ROC) curve suggested that the sensitivity and specificity of miR-146a-5p in predicting PSD were 0.703 and 0.811, respectively. The human miR-146a-5p sequence was highly conserved, with a total of 43 target genes. It involved analysis of activity, signaling pathways, and transcriptional regulation, as well as related signaling pathways such as Toll-like receptors (TLR), neurotrophic factors, and nuclear factor kappa-B (NF-κB). In conclusion, the expression level of miR-146a-5p was abnormally increased in PSD patients, and it could be taken as a candidate marker for the diagnosis of PSD. miR-146a-5p could affect PSD through signaling pathways of TLRs, neurotrophic factors, and NF-κB.